Natural and anthropogenic noise shape bat activity and sonar behavior - Ryan Vosbigian; Ryan Wardle; Hannah S. Rempel; Ellie Brauer; Michael Huggins; Samantha West; Joshua S. Willems; Clinton D. Francis (Ecosphere)
Abstract As human development has expanded, so has the prevalence of anthropogenic noise, which can interfere with acoustic channels used by wildlife. However, since landscapes contain natural sources of persistent noise from features such as rivers, animals may be preadapted to cope with novel human‐generated noise. Comparing how animals respond to anthropogenic and natural noise with similar properties can provide insight into how and why animals may respond to increasing noise pollution. Here, we studied whether Mexican free‐tailed bats (Tadarida brasiliensis) alter activity and call features in response to playback of traffic and river noise relative to ambient acoustics. We observed higher call activity during ambient and traffic playback compared with river playback conditions. These findings suggest that T. brasiliensis may select areas based on acoustic properties and not by associating river sounds with more favorable habitat. We also observed that T. brasiliensis modified call duration and frequency in response to river playbacks in a manner consistent with a behavioral switch from foraging to navigating. Overall, we found evidence that temporal patterning of noise may strongly influence bat activity and that signaling in noise may involve trade‐offs among call features.